Physical, chemical and histological characterization of pectoralis major muscle of broilers affected by wooden breast myopathy - de Oliveira, Rodrigo Fortunato [UNESP] (2021)
This study aimed to characterize the effects of wooden breast myopathy (WBM) on quality of broiler chicken breast meat. Normal samples (absence of myopathy), moderate‐degree samples (hardness only in one area of the breast fillet) and severe‐degree samples (hardness throughout the breast fillet) were classified. In macroscopic analysis, the pectoral muscle affected by the WBM showed, in general, pale color with stiff, irregular and reddish regions (suffusions and petechiae), with the presence of white striations. In microscopic analysis, the myopathy was characterized by loss of the polygonal aspect of the muscle fibers. Samples with moderate degree of the myopathy showed greater (p = 0.0266) water retention capacity. There was an increase (p = 0.004) in total collagen concentration in samples from the severe‐degree group 0.29% in normal samples to 0.43 and 0.48% in samples from moderate‐ and severe‐degree groups, respectively. Samples of chicken breast affected by the severe‐degree WBM showed lower (p < 0.0001) myofibrillar fragmentation index (64.51) and lower (p = 0.0002) fat concentration (2.17%) than normal chicken samples (80.45 and 3.79%, respectively). Samples affected by WBM are larger and heavier and present poorer physical quality when compared to normal chicken meat. Histologically it is possible to observe loss of the polygonal aspect of muscle fibers.